How clean is your house? A study of house dust mites, allergens and other contents of dust samples collected from households. Issue 4 (4th July 2018) - Casley, Lucy S.; Godec, Tom; Logan, James G.; Pearce, James C.; Smith, Hugh M. P.; Stewart, Sophie A.; Dewhirst, Sarah Y.
ABSTRACT: Household dust contains an array of constituents, including house dust mites (HDM) and the HDM allergen, Der p 1, which can cause sensitivities such as asthma and eczema. Vacuuming can help alleviate symptoms, yet little is understood about cleaning behaviour in different households. This pilot study investigated the contents of dust from four household types (students; over 65 s; and families with and without pets). This was then related to cleaning behaviours and perceptions of cleanliness. Our investigation found that HDMs and Der p 1 were present in all households and sampling locations, including participants' cars. The median Der p 1 was greatest in the living room, though results varied. Demographic group was a determinant for the number of human and pet hairs present in dust. Surprisingly, vacuuming was the most disliked task overall. This information requires consideration when developing cleaning products and advising individuals with dust-related health issues.